The Effect Of Excellent Service On Public Satisfaction In Jalaksana Subdistrict - Nadila Siddiqah; Siti Khumayah; Sri Wulandari (ann4publisher@gmail.com, 2026)
Background, Public services are one of the government’s responsibilities that must be carried out to meet the needs of the public. In daily life, the public constantly relies on the services provided by government agencies. Good service is one indicator of the government’s success in carrying out its duties. When the public feels that their lives are made easier and they receive satisfactory service, their trust in the government will increase. Aims, This study aims to determine the extent of the impact of excellent service on public satisfaction. Methods, This study employs a quantitative method involing 56 respondents selected from a population of 70 people using convenience sampling. Data were collected through questionnaires,observation,,documentatiom, and literature study. The data were analyzed using validity and reliability tesst, simple linear regression analysis, and hypothesis testing(t-test). Result, The research results indicate that all statements in the questionnaire were found to be valid and reliable, making them suitable for use as a research instrument. Based on the results of the hypothesis test, a calculated t-value of 4.359 was obtained, which is greater than the critical t-value of 2.004, with a significance level of 0.000—less than 0.05. These results indicate that excellent service has a positive and significant effect on public satisfaction. Conclusion, It can be concluded that excellent service has a significant impact on public satisfaction in Jalaksana Subdistrict. Therefore, service quality must continue to be improved so that the public feels comfortable, trusts the government, and is satisfied with the services provided.